IMPLEMENTASI MODEL CONTEXTUAL TEACHING LEARNING DALAM MENINGKATKAN KETERLIBATAN SISWA PADA PEMBELAJARAN MATEMATIKA - Ulfa, Risna Amalia; Cipta, Dyah Ayu Sulistyaning (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
This best practice writing aims to determine the effectiveness of the CTL learning model in increasing student involvement in learning mathematics and to provide the best recommendations for using Contextual Teaching Learning in learning. Learning problems that occur in SMA Selamat Pagi Indonesia class XII students involving conditions of low learning motivation and lack of involvement in all learning activities, of course, have an impact on learning outcomes that do not achieve learning objectives. The method used in this research is using qualitative methods where data collection through literature review, observation, interviews, and documentation, then analyzed with a SWOT matrix equipped with IFAS (Internal Factor Analysis Strategy) and EFAS (External Factor Analysis Strategy) factors. The use of the CTL model has been able to show significant results, in the SWOT matrix shows that the results of the analysis of internal and external factors, positioning the use of CTL in learning in Quadrant 1. Which means, the use of CTL is in a very favorable situation. The use of this learning model has opportunities and strengths at a positive value (x = +1.22, y = +1.17). The strategy that must be applied in using the CTL model is to support an aggressive growth policy (Growth oriented strategy), which is fully implemented and disciplined according to its syntax, so that its implementation can be effective in increasing student involvement in learning mathematics.